Epidemiology and clinical presentation of kidney amyloidosis have changed over the past three decades: a nationwide population-based study - Hilde J. Vasstrand; Melinda Raki; Rannveig Skrunes; Sabine Leh; Janne Thomsen; Helga Gudmundsdottir; Arnljot Tveit; Anders Hartmann; Anna V. Reisæter; Anders Åsberg; Tale N. Wien (BMC Nephrology)
Abstract Background Early diagnosis of kidney amyloidosis is essential for optimal treatment and improved outcomes. This large, nationwide cohort spanning three decades, explores the changing epidemiology and clinical presentation of kidney amyloidosis in Norway, aiming to raise amyloid awareness. Methods In the 30-year period (1988–2017), we identified 479 patients with biopsy-confirmed kidney amyloidosis from national registries. Past medical records were reviewed for additional amyloid relevant data and cases were divided into groups of non-AA and AA amyloidosis. Results Overall amyloid biopsy incidence in the registries was stable around 4%, but a shift in types occurred. The AL-dominated non-AA group increased from 1.9% to 2.8% (p = 0.014) while the AA group decreased from 2.6% to 1.3% (p < 0.001). The change in AA was related to less rheumatic disease, partly compensated by an increase in AA in people who inject drugs. The scope and accuracy of amyloid typing improved in the study period, significantly reducing undetermined cases (p < 0.001) and providing more robust diagnoses. Clinical presentation was diverse, but proteinuria was present in 94%. Non-AA patients more often than AA had nephrotic syndrome (70% vs 51%, p < 0.001) and better-preserved kidney-function (median (IQR) eGFR 53(55) vs 27(34) ml/min/1.73 m2, p < 0.001). AA patients were younger (p < 0.001) with higher prevalence of hypertension (53% vs 38%, p < 0.001). Notably, AA in people who inject drugs was more advanced and near half presented with end-stage kidney disease. In recent years, non-AA presented with significantly improved serum albumin (p = 0.002), haemoglobin (p = 0.020) and erythrocyte sedimentation ratio (p = 0.029). Additionally, the percentage of non-AA with end-stage kidney disease fell from 26.8% to 8.7% (p = 0.005), possibly indicating earlier diagnosis. Conclusion The epidemiology of kidney amyloidosis has changed over the past 30 years. Biopsy incidence of non-AA is increased, and findings may suggest an earlier diagnosis. Amyloid typing has improved over time and is reflected in more precise amyloid diagnoses and reduced number of undetermined cases in recent years. Although AA related to rheumatic disease is declining, AA amyloidosis in people who inject drugs represents a growing challenge. The changing epidemiology of kidney amyloidosis may impact clinical presentation and future healthcare needs, emphasising the need for amyloid awareness.